Atopic dermatitis and its relation to food allergy. Issue 3 (June 2020) - Graham, François; Eigenmann, Philippe A.
Abstract : Purpose of review: To present the most recent evidence on atopic dermatitis and its relation to food allergy. Recent findings: Atopic dermatitis is a chronic inflammatory disorder of the skin characterized by impaired skin barrier because of multifactorial causes including genetic factors, immune dysregulation, and skin microbiome dysbiosis. Infants with temporary skin barrier disruption and/or persistent atopic dermatitis are particularly at risk of developing food allergy (during the so-called atopic march), with up to half of patients demonstrating positive food-specific IgE and one-third of severe cases of atopic dermatitis having positive symptoms on oral food challenge. A high proportion of children with atopic dermatitis exhibit asymptomatic sensitization to foods, and skin testing to identify potential food triggers is not recommended unless the patient has a history suggestive of food allergy and/or moderate-to-severe atopic dermatitis unresponsive to optimal topical care. Indeed, indiscriminate testing can lead to a high proportion of false-positive tests and harmful dietary evictions. Promising strategies to prevent food allergy in children with atopic dermatitis include early skincare with emollients and treatment with topical steroid, and early introduction of highly allergenic foods. Summary: Further studies are required to identify risk factors for atopic dermatitis to help prevent the development of food allergy in this high-risk population.